Use of social media and Work Collaboration - Sukamto Sukamto; Andika Baskara (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to determine the extent to which the use of social media has an influence on knowledge sharing, absorption capacity, and collaboration of state civil servants (SCS). This study uses a quantitative descriptive method with a survey method on employees in the Central Java Provincial Government. The results of the study show that the use of social media increases knowledge sharing, absorption capacity, and collaboration in organizations. So it is necessary to strengthen the use of social media in work organizations and make rules for the use of media that can encourage collaboration and organizational performance. The limitation of this research is that this research is carried out on the civil apparatus of the Central Java Province in all parts, in the future it is necessary to conduct research in more specific fields or sections.